Leader humility in Singapore - OC, Burak (Institutional Knowledge at Singapore Management University, 2015)
The theoretical development and empirical testing of the effects of humility in the organizational sciences is surprisingly rare. This is especially pronounced in the study of leadership in Asian contexts. To address this we employ a qualitative approach to examine the conceptualization of leader humility in Singapore and assess whether this conceptualization differs from other emerging conceptualizations of leader humility. In Study I, using semi-structured interviews of 25 Singaporeans, we identified nine major dimensions of humble leader behaviors and explored our participants' beliefs about culturally-based differences in leader humility. In Study 2 (N = 307), we generalized our findings to a broader sample and explored how the nine dimensions fit with existing taxonomies. In addition to replicating all of the Western conceptual dimensions of humility, we identified five unique dimensions of behaviors indicative of leader humility in Singapore. (C) 2014 Elsevier Inc. All rights reserved.